Vasculitis in Juvenile-Onset Systemic Lupus Erythematosus - Smith, Eve M. D.; Lythgoe, Hanna; Hedrich, Christian M. (Frontiers in Pediatrics, 2019)
Juvenile-onset systemic lupus erythematosus (JSLE) is a rare, heterogeneous multisystem autoimmune disease that can affect any organ, and present with diverse clinical and serological manifestations. Vasculitis can be a feature of JSLE. It more commonly presents as cutaneous vasculitis than visceral vasculitis, which can affect the central nervous system, peripheral nervous system, lungs, gut, kidneys, heart and large vessels. The incidence and prevalence of vasculitis in JSLE has not been well described to date. Symptoms of vasculitis can be non-specific and overlap with other features of JSLE, requiring careful consideration for the diagnosis to be achieved and promptly treated. Biopsies are often required to make a definitive diagnosis and differentiate JSLE related vasculitis from other manifestations of JSLE, vasculopathies and JSLE related antiphospholipid syndrome. Visceral vasculitis can be life threatening, and its presence at the time of JSLE diagnosis is associated with permanent organ damage, which further highlights the importance of prompt recognition and treatment. This review will focus on the presentation, diagnosis, management and outcomes of vasculitis in JSLE, highlighting gaps in the current evidence base.